Practical Applications of a Vision-based Robot for Security and Safety of Tailings Tunnels Infrastructure in the Mining Industry - Ramirez J. (2021)
ACKNOWLEDGMENT This work was financial supported by Concytec-The World Bank Project ”Improvement and Expansion of Services of the National System of Science, Technology and Technological Innovation” 8682-PE, through its executing unit Fondecyt under contract No. 054-2018-FONDECYT- BM-IADT-AV.Furthermore, the authors thank the support of the Pontificia Universidad Catolica del Peru and the Center for Autonomous Systems of the Sydney University of Technology for the support provided during the execution of the research project.